DETERMINANTS OF GROWTH OF MUDHARABAH DEPOSITS IN SHARIA COMMERCIAL BANKS IN INDONESIA - Mufidah, Ana; Puspitasari, Novi; Melaty, Sophis (MBA : Journal of Management and Business Aplication, 2022)
The growth of mudharabah deposits is the level of deposit of funds by Islamic bank customers (creditors) for a certain period of time using the profit sharing principle. This study will empirically examine the effect of profit sharing, financing to deposit ratio (FDR), net performing loan (NPF), and bank size as independent variables (X) on the growth of mudharabah deposits at Islamic Commercial Banks in Indonesia. 2016-2019 years. The population used in this thesis research is the entire population of Islamic Commercial Banks (BUS) in Indonesia and registered with the Financial Services Authority. The sample in this study was all Islamic Commercial Banks in Indonesia, which amounted to 14 BUS in 2016- 2019 with sensus method. The data analysis method used in this research is descriptive statistical method with multiple linear regression analysis. The results of this study that the profit sharing ratio (TBH) has no significant effect , The liquidity ratio (FDR) has a significant effect , The NPF ratio has no significant effect and The bank size ratio (SIZE) has a significant effect on the variable growth of mudharabah deposits (Y) at Islamic Commercial Banks in Indonesia.